Within-person examination of the exercise intention-behavior gap among women in midlife with elevated cardiovascular disease risk. (May 2022) - Arigo, Danielle; Hevel, Derek; Bittel, Kelsey; Maher, Jaclyn P.
Abstract: Engaging in moderate-to-vigorous intensity physical activity (MVPA) is important for protecting cardiovascular health among women in midlife (i.e., ages 40–60)-particularly if they have already developed conditions that increase their risk for cardiovascular disease (e.g., hypertension). Although the gap between MVPA intentions and behavior is well documented in other populations, little is known about the intention-behavior gap in this at-risk group, particularly as it plays a role in daily life. The present study employed an ecological momentary assessment design to examine the relation between women's MVPA intentions and behavior in the subsequent 3 h, as well as momentary moderators of this relation (i.e., affective states and body satisfaction). Surveys sent to women's smartphones 5 times per day for 10 days while they wore ActiGraph GT3X waistband accelerometers. Women achieved their exercise intentions at only 13% of occasions on which they set such intentions. Although the most common intended exercise was walking, women engaged in more minutes of MVPA after setting intentions to do yoga or Pilates than any other type of exercise ( sr  = 0.25). Multilevel models showed a modest within-person relation between minutes of intended MVPA and observed MVPA in the next 3 h ( sr  = 0.20). This relation was moderated within-person by the reported extent of positive affect (particularly contentment) and body satisfaction ( sr s = 0.35 and 0.28, respectively). Findings extend knowledge about the physical activity intention-behavior gap to an at-risk population of women and identify positive affect and body satisfaction as potential contextual influences for this group, which could inform improvements to existing interventions (e.g., delivering intervention content at times with lower-than-usual body satisfaction). Highlights: Women in midlife with CVD risk regularly set exercise intentions in daily life. These women achieve their exercise intentions on only 13% of occasions. Intended exercise is weakly associated with subsequent exercise behavior. This gap is smaller when women experience low contentment and body satisfaction.